Geochemical Characteristics of Iron Sand Deposits in Karsut Beach Area, Jeneponto Regency, South Sulawesi Province - Birrul Waalidain, Alif; Harwan, Harwan; Aswadi, Muhammad (Journal of Geology and Exploration, 2024)
Iron sand is one of the industrial minerals. Iron sand ini Indonesia is still limited to being used as a raw material for cement factories in the manufacture of concrete. Iron is given the symbol (Fe) in the periodic table's chemical element. The purpose of this study was to determine the mineral properties of iron sand and the chemical characteristics of iron sand. The research location is in Jeneponto, Jeneponto is a district in the province of South Sulawesi, Indonesia. The stages of the sampling method are carried out by measuring the distance of each sample hole. From one point to another, within 10 meters with a depth of 30cm each from the surface after that the sample that has been taken is then dried. This research method uses XRD and XRF analysis methods. From the results of the why XRD analysis, it was found that 2 minerals carrying iron sand, including Magnetite and Hematite with the percentage content of these minerals, are. Magnetite mineral (Fe3O4) 40,0% and Hematite mineral (Fe2O3) 37,7%. From the results of XRF analysis shows that the chemical composition contained in Fe2O3 minerals contains oxide and hydroxide elements Fe, O, Oxide is a chemicali compound that contains at leasti one oxygen atom and at least one other element.